Severe hypoxemia during veno-venous extracorporeal membrane oxygenation: exploring the limits of extracorporeal respiratory support (Clinics, 2014)
OBJECTIVE: Veno-venous extracorporeal oxygenation for respiratory support has emerged as a rescue alternative for patients with hypoxemia. However, in some patients with more severe lung injury, extracorporeal support fails to restore arterial oxygenation. Based on four clinical vignettes, the aims of this article were to describe the pathophysiology of this concerning problem and to discuss possibilities for hypoxemia resolution. METHODS: Considering the main reasons and rationale for hypoxemia during veno-venous extracorporeal membrane oxygenation, some possible bedside solutions must be considered: 1) optimization of extracorporeal membrane oxygenation blood flow; 2) identification of recirculation and cannula repositioning if necessary; 3) optimization of residual lung function and consideration of blood transfusion; 4) diagnosis of oxygenator dysfunction and consideration of its replacement; and finally 5) optimization of the ratio of extracorporeal membrane oxygenation blood flow to cardiac output, based on the reduction of cardiac output. CONCLUSION: Therefore, based on the pathophysiology of hypoxemia during veno-venous extracorporeal oxygenation support, we propose a stepwise approach to help guide specific interventions.